VR-Based Robot Programming and Simulation System for an Industrial Robot - Jen, Yap Hwa; Taha, Zahari; Vui, Lee Jer (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Traditional robot programming such as teach by lead etc have been used for many years. These methods are considered not efficient and outdated in the current industrial and market demands. In this paper, virtual reality (VR) technology is used to improve human-robot interface - no complicated command or programming knowledge is required. The system is divided into three major parts: task teaching by demonstration in a computer generated virtual environment, a graphical robot simulator with intelligent robot command generator and last but not least, real task execution. The user is requested to complete the desired task in a virtual teaching system by wearing a data glove attached with a sensor tracker. The process path will be simulated and analyzed to obtain the optimum trajectory. Robot motions can be checked through the simulation program and robot program can be generated for the real task execution.